Impact of Consensus Conference Review on Diagnostic Disagreements in the Evaluation of Cervical Biopsy Specimens. Issue 5 (19th April 2017) - Layfield, Lester J.; Hammer, Richard D.; Frazier, Shellaine R.; Esebua, Magda; Bivin, William W.; Laziuk, Katsiaryna; Nguyen, Van T.; Johannesen, Eric; Schmidt, Robert L.
Abstract: Objectives: To determine the impact of consensus conferences on the frequency of discrepant cases in a surgical pathology practice. Methods: The percentage of discrepancies in cases reviewed at a weekly consensus conference was calculated for the first and last months of a 13-month period. Both interrater agreement and agreement with the consensus diagnoses were assessed. A total of 309 diagnoses were performed for the first month and 518 for the last month. Both absolute and chance-corrected agreement were calculated for each period. Results: Absolute agreement rate increased from 91.2% in the first month to 98.2% in the final month. Chance-corrected agreement increased from 0.80 in the first month to 0.97 in the final month. Conclusions: The consensus conference technique appears to be a useful method to reduce intradepartmental diagnostic discrepancies. Both absolute and chance-corrected agreement are improved by using consensus conferences.